Toxic Anterior Segment Syndrome with Intracameral Moxifloxacin: Case Report and Review of the Literature. (2nd March 2021) - Amireskandari, Annahita; Bean, Andrew; Mauger, Thomas
Abstract : A case of severe anterior segment toxicity secondary to high-volume, undiluted intracameral moxifloxacin for endophthalmitis prophylaxis is reported. We examine the other reported cases of toxicity after intracameral moxifloxacin, as well as iris depigmentation and transillumination syndromes after oral and topical fluoroquinolone exposure. Additionally, we review the literature on safety, efficacy, and appropriate dosing of intracameral antibiotics with a focus on moxifloxacin.